2000
DOI: 10.1007/s004680000068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought on photoprotective mechanisms in European beech (Fagus sylvatica L.) seedlings from different provenances

Abstract: The effects of drought on photoprotection mechanisms of three beech provenances from three contrasting climatic origins have been studied. Morphology differed among provenances, with a lower leaf area/fine roots ratio in the xeric populations (Moncayo). This characteristic allowed this provenance to respond later than the others to a drought-stress treatment. However, in desiccating leaves the stability of PSII was higher in the plants from the stressful climate of the Pyrenees (Belagoa). Drought resulted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 20 publications
5
63
0
Order By: Relevance
“…This classification of oak in relation to beech is consistent with other studies that have documented the higher physiological performance of oak under conditions of water shortage [52,99]. The root-to-shoot ratios measured in this study were in accordance with values determined for F. sylvatica [100], but slightly higher for Q. petraea than in other studies [101].…”
Section: How Resistant To Drought Are Seedlings Of the Minor Tree Spesupporting
confidence: 82%
“…This classification of oak in relation to beech is consistent with other studies that have documented the higher physiological performance of oak under conditions of water shortage [52,99]. The root-to-shoot ratios measured in this study were in accordance with values determined for F. sylvatica [100], but slightly higher for Q. petraea than in other studies [101].…”
Section: How Resistant To Drought Are Seedlings Of the Minor Tree Spesupporting
confidence: 82%
“…This would be detected on the next morning only if stresses were strong enough and/or repair capacity during the night was weak (Verhoeven et al 1999;Adams et al 2001Adams et al , 2004Llorens et al 2003;Zarter et al 2006). Reports have indicated that, in low temperature (Ottander et al 1995;Verhoeven et al 1996;Barker et al 2002) or water stress (Demmig et al 1988;García-Plazaola and Becerril 2000), retained zeaxanthin ? antheraxanthin always accompanied a low F v /F m .…”
Section: Resultsmentioning
confidence: 93%
“…Several observations support this state, e.g., α-tocopherol increases remarkably by water deficit in spinach and pea leaves (Tanaka et al, 1990;Moran et al, 1994), in wheat (Bartoli et al, 1999), in Mediterranean shrubs such as rosemary and lavender (Munne-Bosch et al, 1999;Munne-Bosch et al, 2001), and in European beech seedlings (Garcia-Plazaola and Becerril, 2000). However an interesting observation can be also taken; the changes in α-tocopherol level during plant responses to environmental stress are characterized by two phases.…”
Section: -2-2-tocopherols (Vitamin E)mentioning
confidence: 85%